Preparation method of bimetallic cation doped modified starch-based hard carbon material, starch-based hard carbon material and application of starch-based hard carbon material
Through the preparation method of dual -metal cation doped and modified starch -based hard carbon materials, the problem of insufficient sodium storage and low chemical stability of hard carbon negative electrode materials, and realized the preparation of high -performance starchy -based hard carbon materials. It is suitable for sodium sodium. The negative electrode material of ion batteries improves the large -scale application potential of sodium ion batteries.
Patent Information
- Application Number
- CN202411268321.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing hard carbon anode materials have insufficient sodium storage performance in sodium ion batteries, and the doping of inorganic non-metallic anions may introduce defects and impurities, affecting the electron transport and chemical stability of the material.
A method for preparing bimetallic cation-doped modified starch-based hard carbon materials is adopted, by dissolving cellulose, acid and metal chloride in water to form a mixed solution, then adding starch and performing drying, low-temperature pre-calcination and high-temperature calcination. Produce starch-based hard carbon materials with controllable particle size.
The excellent electrochemical properties of amyloid -based hard carbon materials have the advantages of controllable particle size, low cost, and easy industrialization. It is suitable for the negative electrode material of sodium ion battery, which enhances the large -scale application potential of sodium ion batteries.
Smart Images

Figure CN119349543A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and in particular relates to a preparation method of a bimetallic cation-doped modified starch-based hard carbon material, a starch-based hard carbon material and applications thereof. Background Art
[0002] Among the negative electrode materials of sodium-ion batteries, carbon-based materials have become the preferred research target for sodium storage negative electrode materials because of their advantages such as wide sources, rich resources, and diverse structures. Carbon materials can be divided into graphite-like carbon materials (mainly graphite), new carbon materials, and amorphous carbon materials according to their microstructures. Among them, the disordered structure of hard carbon makes it have more defects and vacancies, that is, more active sites for sodium storage; and its interlayer spacing is larger, which is more suitable for the storage and deintercalation of sodium ions, and can maintain good stability during the sodium ion deintercalation process. Therefore, compared with other carbon materials and non-carbon materials, hard carbon is more suitable for use as a negative electrode material for sodium-ion batteries. In addition, due to the excellent innate conditions of hard carbon (wide sources, simple preparation, etc.), it has become the only choice for commercial negative electrode materials for sodium-ion batteries. Therefore, the preparation of high-performance hard carbon negative electrode materials is of great significance to the large-scale application of sodium-ion batteries.
[0003] As an amorphous carbon material, hard carbon is usually composed of a large number of disordered graphite crystallites and amorphous regions, similar to a "house of cards" structure, and there is no precise crystal structure model. Therefore, it is difficult to theoretically study the physical and chemical changes in the sodium insertion / deintercalation process of hard carbon. The mechanism models that have been proposed include "intercalation-pore filling", "adsorption-intercalation", "adsorption-pore filling", "adsorption-intercalation / pore filling", etc. In general, the sodium storage behavior of hard carbon materials mainly includes: (1) adsorption of surfaces, defect sites and functional groups; (2) micropore filling; (3) intercalation of graphitized carbon layers. At present, the preparation of hard carbon materials, academic research and commercial exploration all use inorganic non-metallic anions (N, P, S, O, etc.) to improve the sodium storage performance of hard carbon negative electrode materials. However, the doping of inorganic non-metallic anions may introduce defects or impurities, thereby affecting the electron transport path of hard carbon materials and causing the chemical stability of the materials to decrease. At the same time, this type of doping requires special process steps and technical control, which increases the complexity of preparation and also increases the production cost. Summary of the invention
[0004] In order to obtain a new type of hard carbon negative electrode material, the present invention provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material. The method uses low-cost starch as the main raw material, and prepares a starch-based hard carbon material with controllable particle size through the doping modification of bimetallic cations and the synergistic effect. The prepared starch-based hard carbon material has excellent electrochemical properties and can be used as a negative electrode material for sodium ion batteries, which is of great significance to the large-scale application of sodium ion batteries.
[0005] The present invention also provides a bimetallic cation-doped modified starch-based hard carbon material and application thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material, the preparation method comprising:
[0008] dissolving cellulose, acid and two metal chlorides in water to obtain a mixed solution;
[0009] Dispersing starch in the mixture solution to obtain a starch suspension slurry;
[0010] Drying the starch suspension slurry to obtain a precursor powder;
[0011] Pre-calcining the precursor powder at a low temperature in an oxygen or air atmosphere to obtain a hard carbon intermediate;
[0012] The hard carbon intermediate is placed in an inert atmosphere and subjected to high temperature calcination to obtain a bimetallic cation-doped modified starch-based hard carbon material;
[0013] Wherein, the mass ratio of the starch to the cellulose is (3-10):1;
[0014] The two metal chlorides include any two of manganese chloride, sodium chloride, lithium chloride, copper chloride, zinc chloride, aluminum chloride, potassium chloride, calcium chloride and magnesium chloride.
[0015] Furthermore, dissolving cellulose, acid and two metal chlorides in water to obtain a mixed solution specifically comprises:
[0016] Dissolving cellulose, acid, metal chloride A and metal chloride B in water to obtain a transparent mixed solution;
[0017] Wherein, in the mixed solution, the mass concentration of the cellulose is 0.1-1 g / L, the molar concentration of the metal chloride A is 0.01-0.1 mol / L, and the molar concentration of the metal chloride B is 0.01-0.1 mol / L.
[0018] Further, the acid includes at least one of phosphoric acid, hydrochloric acid, nitric acid, sulfuric acid, perchloric acid and acetic acid;
[0019] In the mixed solution, the molar concentration of the acid is 0.1 to 1 mol / L.
[0020] Further, the starch includes at least one of corn starch, mung bean starch, potato starch, wheat starch, sweet potato starch, lotus root starch, pea starch, coconut starch and soluble starch;
[0021] The cellulose comprises at least one of microcrystalline cellulose, polymerized cellulose, lignin fiber, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose;
[0022] The solid content of the starch suspension slurry is 5-60wt%.
[0023] Furthermore, the starch suspension slurry is dried to obtain a precursor powder, which specifically includes:
[0024] The starch suspension slurry is spray-dried to obtain a precursor powder.
[0025] Preferably, the fan frequency of the spray drying is 10-60 Hz, the feed rate is 10-2000 mL / h, the inlet air temperature is 100-275°C, and the outlet air temperature is 60-200°C.
[0026] Further, the precursor powder is pre-sintered at a low temperature in an oxygen or air atmosphere to obtain a hard carbon intermediate, specifically comprising:
[0027] The precursor powder is pre-calcined at a low temperature in an oxygen or air atmosphere, wherein the pre-calcination temperature is 80 to 300° C. and the heat preservation time is 1 to 15 hours to obtain a hard carbon intermediate.
[0028] Furthermore, the hard carbon intermediate is placed in an inert atmosphere for high-temperature calcination to obtain a bimetallic cation-doped modified starch-based hard carbon material, specifically comprising:
[0029] The hard carbon intermediate is placed in an inert atmosphere for high-temperature calcination, wherein the high-temperature calcination includes a first stage and a second stage, wherein the first stage calcination temperature is 500-750° C. and the duration is 1-6 hours, and the second stage calcination temperature is 900-1500° C. and the duration is 1-7 hours, to obtain a bimetallic cation-doped modified starch-based hard carbon material;
[0030] Wherein, the inert atmosphere includes any one of nitrogen, argon, argon-hydrogen mixed gas and nitrogen-hydrogen mixed gas.
[0031] Based on the same inventive concept, the present invention provides a bimetallic cation-doped modified starch-based hard carbon material, and the starch-based hard carbon material is prepared by the above-mentioned preparation method of a bimetallic cation-doped modified starch-based hard carbon material.
[0032] Based on the same inventive concept, the present invention also provides an application of a bimetallic cation-doped modified starch-based hard carbon material in the preparation of a negative electrode material for a sodium ion battery.
[0033] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0034] 1. The present invention discloses a method for preparing a starch-based hard carbon material doped with modified bimetallic cations. The method uses starch with low cost as the main raw material, adopts a simple solution method to achieve the doping of bimetallic ions, and prepares starch-based hard carbon materials with controllable particle size through the doping modification of bimetallic cations and the synergistic effect. The method has the advantages of simple process, low cost, environmental friendliness and convenience for mass production. The prepared starch-based hard carbon material has excellent electrochemical properties, and has the advantages of controllable particle size, low cost and easy industrialization. It can be used as a negative electrode material for sodium ion batteries, which is of great significance to the large-scale application of sodium ion batteries.
[0035] 2. The present invention discloses a method for preparing a bimetallic cation-doped modified starch-based hard carbon material. In the mixed solution prepared by the method, cellulose is dissolved in a multi-metal salt solution as a glucose polymer with a smaller molecular weight. These small molecules form a soluble complex structure with the metal ions. During the high-temperature calcination process, these complex structures will carry the metal ions to coat the hard carbon surface formed by the starch, thereby achieving a certain degree of inhibition of the foaming phenomenon of the starch during the high-temperature pyrolysis process. The present invention uses a mixture of starch and cellulose as a hard carbon precursor, wherein starch with a wide source and uniform composition provides the main hard carbon skeleton. After the cellulose is dissolved, it forms a complex structure with the metal ions and can be coated on the starch surface, which is beneficial to improving the rate performance of the hard carbon.
[0036] 3. The present invention discloses a bimetallic cation-doped modified starch-based hard carbon material. Through the doping of metal ions, the metal ions will form an M-Nx-C (M represents metal, N is nitrogen, C is carbon, and x represents quantity) structure during the carbonization and pyrolysis process to repair the defects on the hard carbon surface and provide more effective active sites. At the same time, the presence of metal ions increases the interlayer spacing and closed-pore diameter of the hard carbon material, thereby effectively improving the sodium storage capacity and the first coulomb efficiency of the hard carbon. In addition, the present invention adopts bimetallic ion doping and utilizes the bimetallic synergistic effect. While inhibiting the graphitization of hard carbon, it can also repair the problem of large defects in the hard carbon itself, inhibit the decomposition of the electrolyte, and form a dense and uniform SEI film on the hard carbon surface. The starch-based hard carbon material of the present invention has a reversible discharge capacity of 400mAh / g and a first coulomb efficiency of more than 90%, and has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 This is the XRD diagram of the hard carbon negative electrode material prepared in Examples 1-4 of the present invention.
[0039] Figure 2 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 1 of the present invention.
[0040] Figure 3 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 2 of the present invention.
[0041] Figure 4 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 3 of the present invention.
[0042] Figure 5 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0043] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0044] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0046] The technical principle of the present invention is as follows:
[0047] The present invention provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material, the preparation method comprising:
[0048] S1. dissolving cellulose, acid and two metal chlorides in water to obtain a mixed solution;
[0049] S2. dispersing starch in the mixture solution to obtain a starch suspension slurry;
[0050] S3. drying the starch suspension slurry to obtain a precursor powder;
[0051] S4. The precursor powder is pre-sintered at a low temperature in an oxygen or air atmosphere to obtain a hard carbon intermediate;
[0052] S5. The hard carbon intermediate is placed in an inert atmosphere and calcined at a high temperature to obtain a bimetallic cation-doped modified starch-based hard carbon material;
[0053] Wherein, the mass ratio of the starch to the cellulose is (3-10):1;
[0054] The two metal chlorides include any two of manganese chloride, sodium chloride, lithium chloride, copper chloride, zinc chloride, aluminum chloride, potassium chloride, calcium chloride and magnesium chloride.
[0055] In the present invention, acid is added to the mixed solution because different metal chlorides provide Lewis acid to the solution after being dissolved in water. The addition of a small amount of low-concentration acid can promote the formation of complexes between metal ions and cellulose while providing the required hydrogen ions to the entire system.
[0056] In the present invention, cellulose is dissolved first and then starch is added. This is because starch is also slightly soluble in metal salt solution and reacts under acidic conditions. Adding starch later ensures the uniformity of the hard carbon precursor during pyrolysis and avoids the impact of the reaction on the hard carbon performance.
[0057] In the present invention, the precursor powder is prepared by spray drying, and the dissolved cellulose material is uniformly mixed with starch through spray drying, and the material can be controlled to become uniform spherical particles.
[0058] In the present invention, the precursor powder is pre-fired at a low temperature in an oxygen or air atmosphere, which can reduce costs and inhibit the foaming of starch during pyrolysis. The hard carbon intermediate is placed in an inert atmosphere for high-temperature calcination. This is because the high-temperature carbonization of the redox gas will reduce the fixed carbon content of the hard carbon and react with carbon. An inert atmosphere is a necessary condition for the formation of hard carbon.
[0059] In the present invention, the mass ratio of the starch to the cellulose is (3-10):1, and the starch and the cellulose are mixed together as a hard carbon precursor, which has a wide source and uniform composition.
[0060] In the present invention, the two metal chlorides include any two of manganese chloride, sodium chloride, lithium chloride, copper chloride, zinc chloride, aluminum chloride, potassium chloride, calcium chloride and magnesium chloride, which are low in cost, environmentally friendly and widely available. The present invention adopts bimetallic co-doping and utilizes the bimetallic synergistic effect to suppress the graphitization of hard carbon while also repairing the problem of large defects of hard carbon itself, suppressing the decomposition of electrolyte, and forming a dense and uniform SEI film on the surface of hard carbon.
[0061] Step S1 specifically includes:
[0062] Dissolving cellulose, acid, metal chloride A and metal chloride B in water to obtain a transparent mixed solution;
[0063] Wherein, in the mixed solution, the mass concentration of the cellulose is 0.1-1 g / L, the molar concentration of the metal chloride A is 0.01-0.1 mol / L, and the molar concentration of the metal chloride B is 0.01-0.1 mol / L.
[0064] Further, the acid includes at least one of phosphoric acid, hydrochloric acid, nitric acid, sulfuric acid, perchloric acid and acetic acid;
[0065] In the mixed solution, the molar concentration of the acid is 0.01 to 1 mol / L.
[0066] In the present invention, the advantage of using the above concentration of cellulose in the mixed solution is that it can form complexes with all metal ions.
[0067] The molar concentration of the acid in the mixed solution is 0.01 to 1 mol / L. If the concentration is lower than this range, H + If the capacity is insufficient and the acidity is above this range, it will be too strong and will affect the sodium storage performance of starch after it forms hard carbon, and will also increase the environmental pressure of the process.
[0068] Step S3 specifically includes:
[0069] The starch suspension slurry is spray-dried to obtain a precursor powder.
[0070] Preferably, the fan frequency of the spray drying is 10-60 Hz, the feed rate is 10-2000 mL / h, the inlet air temperature is 100-275°C, and the outlet air temperature is 60-200°C.
[0071] In the present invention, the spray drying process parameters mentioned above can be used to volatilize the water in the solution in time and obtain a suitable spherical precursor. If the process parameters are too low, the water cannot be evaporated in time, making it difficult to collect the precursor material. If the process parameters are too high, starch saccharification will cause adhesion to the instrument surface.
[0072] Step S4 specifically includes:
[0073] The precursor powder is pre-calcined at a low temperature in an oxygen or air atmosphere, wherein the pre-calcination temperature is 80 to 300° C. and the heat preservation time is 1 to 15 hours to obtain a hard carbon intermediate.
[0074] In the present invention, the low-temperature pre-firing temperature is 80-300° C. and the holding time is 1-15 hours, which has the advantage of suppressing the foaming phenomenon during the carbonization process of starch. The purpose of low-temperature pre-firing in an oxygen or air atmosphere is to pre-oxidize starch and promote the starch cross-linking reaction.
[0075] Step S5 specifically includes:
[0076] The hard carbon intermediate is placed in an inert atmosphere for high-temperature calcination, wherein the high-temperature calcination includes a first stage and a second stage, wherein the first stage calcination temperature is 500-750° C. and the duration is 1-6 hours, and the second stage calcination temperature is 900-1500° C. and the duration is 1-7 hours, to obtain a bimetallic cation-doped modified starch-based hard carbon material;
[0077] Wherein, the inert atmosphere includes any one of nitrogen, argon, argon-hydrogen mixed gas and nitrogen-hydrogen mixed gas.
[0078] In the present invention, high-temperature calcination is carried out in two stages. The first stage is for sufficient reaction to completely remove impurities such as tar and gas from the material, and the second stage provides a stable reaction environment based on the first stage.
[0079] The calcination temperature of the first stage is 500-750°C and the duration is 1-6 hours. The advantage is that it can provide enough time to eliminate the generation of impurity gases such as tar in this temperature range. If the calcination temperature is too low, the reaction will be incomplete, and if it is too high, the reaction will be too violent and affect the process of hard carbon evolution.
[0080] The second stage calcination temperature is 900-1500°C and the duration is 1-7 hours, which has the advantage of forming a stable hard carbon material.
[0081] The following is a detailed description of the preparation method of a bimetallic cation-doped modified starch-based hard carbon material of the present application in combination with examples and experimental data.
[0082] Example 1
[0083] This embodiment provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material, comprising the following steps:
[0084] (1) Weigh 6.8 g ZnCl2 and 6.2 g AlCl3, add 500 mL deionized water, and stir continuously at room temperature until the two samples are completely dissolved. Then, add 30 g cellulose to the solution and drop 10 mL 0.05 mol / L dilute hydrochloric acid, and stir continuously until the cellulose is completely dissolved. Then weigh 180 g corn starch and add it to the solution in which the cellulose has been dissolved, and stir continuously to obtain a suspension slurry with a solid content of 30 wt%.
[0085] (2) The suspended slurry was spray dried with a fan frequency of 50 Hz, a feed rate of 360 mL / h, an inlet air temperature of 120° C., and an outlet air temperature of 80° C. to obtain and collect a dry precursor powder.
[0086] (3) The precursor powder is placed in an air atmosphere and pre-fired at 200°C for 8 h at a heating rate of 2°C / min. The low-temperature pre-fired material is placed in an argon atmosphere and calcined at 500°C for 2 h at a heating rate of 2°C / min. The temperature is then raised to 1400°C and calcined for 2 h to obtain a Zn-Al bimetallic ion doped hard carbon material.
[0087] Example 2
[0088] This embodiment provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material, comprising the following steps:
[0089] (1) Weigh 6.8 g ZnCl2 and 6.25 g MnCl3, add 500 mL deionized water, and stir continuously at room temperature until the two samples are completely dissolved. Then, add 30 g cellulose to the solution and drop 10 mL 0.05 mol dilute hydrochloric acid, and stir continuously until the cellulose is completely dissolved. Then weigh 180 g corn starch and add it to the solution in which the cellulose has been dissolved, and stir continuously to obtain a suspension slurry with a solid content of 30 wt%.
[0090] (2) The suspended slurry was spray dried with a fan frequency of 50 Hz, a feed rate of 360 mL / h, an inlet air temperature of 120° C., and an outlet air temperature of 80° C. to obtain and collect a dry precursor powder.
[0091] (3) The precursor powder is placed in an air atmosphere and pre-fired at 200°C for 8 h at a heating rate of 2°C / min. The low-temperature pre-fired material is placed in an argon atmosphere and calcined at 500°C for 2 h at a heating rate of 2°C / min. The temperature is then raised to 1400°C and calcined for 2 h to obtain a Zn-Mn bimetallic ion doped hard carbon material.
[0092] Example 3
[0093] This embodiment provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material, comprising the following steps:
[0094] (1) Weigh 5.8 g NaCl2 and 6.25 g MnCl3, add 500 mL deionized water, and stir continuously at room temperature until the two samples are completely dissolved. Then, add 30 g cellulose to the solution and drop 10 mL 0.05 mol dilute hydrochloric acid, and stir continuously until the cellulose is completely dissolved. Then weigh 180 g corn starch and add it to the solution in which the cellulose has been dissolved, and stir continuously to obtain a suspension slurry with a solid content of 30 wt%.
[0095] (2) The suspended slurry was spray dried with a fan frequency of 50 Hz, a feed rate of 360 mL / h, an inlet air temperature of 120° C., and an outlet air temperature of 80° C. to obtain and collect a dry precursor powder.
[0096] (3) The precursor powder is placed in an air atmosphere and pre-fired at 200°C for 8 h at a heating rate of 2°C / min. The low-temperature pre-fired material is placed in an argon atmosphere and calcined at 500°C for 2 h at a heating rate of 2°C / min. The temperature is then raised to 1400°C and calcined for 2 h to obtain a Na-Mn bimetallic ion doped hard carbon material.
[0097] Example 4
[0098] This embodiment provides a method for preparing a bimetallic cation-doped modified starch-based hard carbon material, comprising the following steps:
[0099] (1) Weigh 5.8 g NaCl and 8.5 g CuCl2 respectively, add 500 mL deionized water, and stir continuously at room temperature until the two samples are completely dissolved. Then, add 30 g cellulose to the solution and drop 10 mL 0.05 mol dilute hydrochloric acid, and stir continuously until the cellulose is completely dissolved. Then weigh 180 g corn starch and add it to the solution in which the cellulose has been dissolved, and stir continuously to obtain a suspension slurry with a solid content of 30 wt%.
[0100] (2) The suspended slurry was spray dried with a fan frequency of 50 Hz, a feed rate of 360 mL / h, an inlet air temperature of 120° C., and an outlet air temperature of 80° C. to obtain and collect a dry precursor powder.
[0101] (3) The precursor powder is placed in an air atmosphere and pre-fired at 200°C for 8 h at a heating rate of 2°C / min. The low-temperature pre-fired material is placed in an argon atmosphere and calcined at 500°C for 2 h at a heating rate of 2°C / min. The temperature is then raised to 1400°C and calcined for 2 h to obtain a Na-Cu bimetallic ion doped hard carbon material.
[0102] Figure 1 The XRD diagram of the hard carbon negative electrode material prepared in Examples 1-4 of the present invention is shown in FIG. Figure 1It can be seen that the prepared bimetallic doped hard carbon materials all show typical hard carbon peaks, and a small amount of metal doping will not be detected by the XRD instrument. From the figure, it can be found that the interlayer spacing calculated by the Bragg equation corresponding to the double angle of d002 is greater than 0.4nm.
[0103] Figure 2 This is a charge and discharge curve of the hard carbon negative electrode material prepared in Example 1 of the present invention. The test method is: the electrode material ratio is: active material: SP: PVDF = 8:1:1, constant current charging and constant current discharging are used, the current density is 25mA / g, and the test is performed at room temperature. Figure 2 It can be seen that the first discharge capacity of the hard carbon negative electrode material is 439.16 mAh / g, the first charge capacity is 400.36 mAh / g, and the first coulombic efficiency is 91.165%.
[0104] Figure 3 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 2 of the present invention. Figure 2 It can be seen that the first discharge capacity of the hard carbon negative electrode material is 432.96 mAh / g, the first charge capacity is 392.214 mAh / g, and the first coulombic efficiency is 90.59%.
[0105] Figure 4 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 3 of the present invention. Figure 2 It can be seen that the first discharge capacity of the hard carbon negative electrode material is 419.569 mAh / g, the first charge capacity is 379.70 mAh / g, and the first coulombic efficiency is 90.498%.
[0106] Figure 5 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 4 of the present invention. Figure 2 It can be seen that the first discharge capacity of the hard carbon negative electrode material is 428.787 mAh / g, the first charge capacity is 389.70 mAh / g, and the first coulombic efficiency is 90.884%.
[0107] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0108] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0109] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a bimetallic cation-doped modified starch-based hard carbon material, characterized in that: The preparation method comprises: dissolving cellulose, acid and two metal chlorides in water to obtain a mixed solution; Dispersing starch in the mixture solution to obtain a starch suspension slurry; Drying the starch suspension slurry to obtain a precursor powder; Pre-calcining the precursor powder at a low temperature in an oxygen or air atmosphere to obtain a hard carbon intermediate; The hard carbon intermediate is placed in an inert atmosphere and subjected to high temperature calcination to obtain a bimetallic cation-doped modified starch-based hard carbon material; Wherein, the mass ratio of the starch to the cellulose is (3-10):1; The two metal chlorides include any two of manganese chloride, sodium chloride, lithium chloride, copper chloride, zinc chloride, aluminum chloride, potassium chloride, calcium chloride and magnesium chloride.
2. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 1, characterized in that: The step of dissolving cellulose, acid and two metal chlorides in water to obtain a mixed solution specifically comprises: Dissolving cellulose, acid, metal chloride A and metal chloride B in water to obtain a transparent mixed solution; Wherein, in the mixed solution, the mass concentration of the cellulose is 0.1-1 g / L, the molar concentration of the metal chloride A is 0.01-0.1 mol / L, and the molar concentration of the metal chloride B is 0.01-0.1 mol / L.
3. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 1 or 2, characterized in that: The acid comprises at least one of phosphoric acid, hydrochloric acid, nitric acid, sulfuric acid, perchloric acid and acetic acid; In the mixed solution, the molar concentration of the acid is 0.1-1 mol / L.
4. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 1, characterized in that: The starch comprises at least one of corn starch, mung bean starch, potato starch, wheat starch, sweet potato starch, lotus root starch, pea starch, coconut starch and soluble starch; The cellulose comprises at least one of microcrystalline cellulose, polymerized cellulose, lignin fiber, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose; The solid content of the starch suspension slurry is 5-60wt%.
5. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 1, characterized in that: The step of drying the starch suspension slurry to obtain a precursor powder specifically comprises: The starch suspension slurry is spray-dried to obtain a precursor powder.
6. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 5, characterized in that: The fan frequency of the spray drying is 10-60 Hz, the feed rate is 10-2000 mL / h, the inlet air temperature is 100-275° C., and the outlet air temperature is 60-200° C.
7. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 1, characterized in that: The step of pre-calcining the precursor powder at a low temperature in an oxygen or air atmosphere to obtain a hard carbon intermediate specifically comprises: The precursor powder is pre-calcined at a low temperature in an oxygen or air atmosphere, wherein the pre-calcination temperature is 80 to 300° C. and the heat preservation time is 1 to 15 hours to obtain a hard carbon intermediate.
8. The method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to claim 1, characterized in that: The step of placing the hard carbon intermediate under an inert atmosphere for high temperature calcination to obtain a bimetallic cation-doped modified starch-based hard carbon material specifically comprises: The hard carbon intermediate is placed in an inert atmosphere for high-temperature calcination, wherein the high-temperature calcination includes a first stage and a second stage, wherein the first stage calcination temperature is 500-750° C. and the duration is 1-6 hours, and the second stage calcination temperature is 900-1500° C. and the duration is 1-7 hours, to obtain a bimetallic cation-doped modified starch-based hard carbon material; Wherein, the inert atmosphere includes any one of nitrogen, argon, argon-hydrogen mixed gas and nitrogen-hydrogen mixed gas.
9. A bimetallic cation-doped modified starch-based hard carbon material, characterized in that: The starch-based hard carbon material is prepared by the method for preparing a bimetallic cation-doped modified starch-based hard carbon material according to any one of claims 1 to 8.
10. Use of a bimetallic cation-doped modified starch-based hard carbon material as claimed in claim 9 in preparing a negative electrode material for a sodium ion battery.
Citation Information
Patent Citations
Preparation method and uses of starch-based composite hard carbon negative electrode material
CN107425215A
Hard carbon microspheres as well as preparation method and application thereof
CN114044508A
Copper-tantalum co-doped hard carbon composite material and preparation method and application thereof
CN115417399A
Method for preparing hard carbon through cooperation of chemical gel and alkaline metal oxide template method and application of hard carbon
CN115974045A
Sodium-ion battery core-shell structure bagasse hard carbon-based negative electrode material and preparation method thereof
CN116332152A
Cited By
Preparation method of SnCo-doped hard carbon composite material and sodium ion battery prepared from SnCo-doped hard carbon composite material
CN120841501A